Understanding consumers' intention in socially responsible purchasing in Malaysia using the theory of reasoned action - Ong, Derek Lai Teik *; Ong, Victor Ching Poh *; Ho, Ooi Tim *; Liew, Chiu Limn *; Liew, Wei Chyi * (World Business Institute, Australia, 2014)
Past researches have demonstrated the effectiveness of theory of reasoned action (TRA) model to predict consumers’ purchase intention. However, many researches scarcely use a psychosocial perspective to predict consumers’ purchase intention. Hence, this study extends existing research by incorporating personal moral norms to gain a better understanding of consumers’ purchase intention for ‘socially responsible’ products in the Malaysian marketplace. Results from 178 respondents indicated that attitudes towards behavior, subjective and personal norms influence consumers’ purchase intention. It is found that personal norms also partially mediate between subjective norm and purchase intention. From the findings, it is recommended that companies (and even the government) encourage socially responsible purchasing through holding more public activities, creating social expectations, better disclosures of corporate social responsibility and providing education regarding socially responsible purchasing. Personal engagement of customers should also be considered to encourage better customer relationship when their views are taken into product development and campaigns.